2022
DOI: 10.2174/0929867329666211221112312
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Mediated Target-specific Drug Delivery in Prostate Cancer: An In-depth Review

Abstract: : Nanotechnology has been extensively exploited for its enormous therapeutics and diagnostics potential in the management of multiple disorders. It employs nanomaterials as drug carriers with enhanced efficacy and limited side effects on normal tissues. A lot of nanomaterials have been studied and produced, imminently reforming the treatment and diagnostics of numerous malignancies including cancer. The purpose of the present study is to explore the role of nanotechnology-based devices/therapies that have a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This can be achieved by the combined use of localized drug delivery methods, and the sustained targeted delivery of cancer drugs with molecular recognition units that can interact directly with receptors that are overexpressed on the surfaces of PC cells. This need has stimulated several studies in which nanotechnology and targeted drugs have been used to develop novel methods for the detection and treatment of PC 13–16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be achieved by the combined use of localized drug delivery methods, and the sustained targeted delivery of cancer drugs with molecular recognition units that can interact directly with receptors that are overexpressed on the surfaces of PC cells. This need has stimulated several studies in which nanotechnology and targeted drugs have been used to develop novel methods for the detection and treatment of PC 13–16 …”
Section: Introductionmentioning
confidence: 99%
“…This need has stimulated several studies in which nanotechnology and targeted drugs have been used to develop novel methods for the detection and treatment of PC. [13][14][15][16] Mesoporous silica nanoparticles have been widely studied as sustained release cancer drug nanocarriers to inhibit cancer cell growth. [17][18][19][20][21] This is due to their unique properties, such as high total specific surface area, high pore volume, large loading capacity, biocompatibility, and easy surface modification.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of multiple therapeutic agents remains challenging, however, in this context nanotechnology applied to drug delivery can offer a series of advantages such as the possibility to combine in a unique carrier system more than one therapeutic agent and to increase the bioavailability of the single components. [7][8][9][10] Furthermore, it has been reported that several nanocarriers can afford implementation of classical chemotherapy with other types of treatment like photodynamic therapy (PDT). [11][12][13][14][15] Combination therapy aims at the synergic action of different therapeutics targeting more than one metabolic pathway in order to maximize the impact of the treatment and eventually improve the therapeutic outcome.…”
Section: Introductionmentioning
confidence: 99%